USE OF NEW PEDAGOGICAL TECHNOLOGIES IN "READING LITERACY" LESSONS AND ITS SCIENTIFIC AND THEORETICAL BASICS - Negmatova Zulayho Shermatovna (Journal Park Publishing, 2024)
The article discusses the advantages of new pedagogical technologies in the educational process, their importance in increasing the effectiveness of education and upbringing, meaningful organization of teacher and student activities, its scientific and theoretical foundations in primary education "Reading literacy" shown on the example of textbooks.
Keywords: innovation, technology, learning, efficiency, educational process, fairy tale, ethnopedagogy.